Validity and redescription of the flathead fish, Onigocia macrocephala (Weber, 1913) (Teleostei: Platycephalidae) - Imamura, Hisashi (Zootaxa, 2012)
After the original description, Platycephalus macrocephalus Weber, 1913 has been rarely treated as a valid species and its taxonomic status has been unclear. It was revealed here that seven syntypes of the species belong to two species and four of them are identical with Onigocia grandisquama (Regan, 1908) but the remaining three specimens are identified as a distinct species of Onigocia Jordan & Thompson, 1913, which has been mistakenly identified as Onigocia macrolepis (Bleeker, 1854) by several authors. One of the three specimens illustrated in the original description is designated as the lectotype of the species. Onigocia macrocephala is separable from its other congeners in having 21–23 (mode 22) pectoral fin rays, 9–10 caudal fin rays, 1 + 4–6 = 5–7 (mode 6) gill rakers, a larger head (38.8–42.3% SL), a single ocular flap present and usually extending slightly beyond the posterior margin of the orbit, a few or several small and short papillae on the posteromedial portion of the eye in larger specimens, the upper iris lappet short and branched, the lachrymal with two distinct antrorse spines anteriorly, a notch on the suborbital ridge below the eye, and no interopercular flap.